Hyperbaric oxygen as a model of lens aging in the bovine lens: The effects on lens biochemistry, physiology and optics. (November 2021) - Lim, Julie C.; Grey, Angus C.; Vaghefi, Ehsan; Nye-Wood, Mitchell G.; Donaldson, Paul J.
Abstract: Age related nuclear (ARN) cataracts in humans take years to form and so experimental models have been developed to mimic the process in animals as a means of better understanding the etiology of nuclear cataracts in humans. A major limitation with these animal models is that many of the biochemical and physiological changes are not typical of that seen in human ARN cataract. In this review, we highlight the work of Frank Giblin and colleagues who established an in vivo animal model that replicates many of the changes observed in human ARN cataract. This model involves exposing aged guinea pigs to hyperbaric oxygen (HBO), which by causing the depletion of the antioxidant glutathione (GSH) specifically in the lens nucleus, produces oxidative changes to nuclear proteins, nuclear light scattering and a myopic shift in lens power that mimics the change that often precedes cataract development in humans. However, this model involves multiple HBO treatments per week, with sometimes up to a total of 100 treatments, spanning up to eight months, which is both costly and time consuming. To address these issues, Giblin developed an in vitro model that used rabbit lenses exposed to HBO for several hours which was subsequently shown to replicate many of the changes observed in human ARN cataract. These experiments suggest that HBO treatment of in vitro animal lenses may serve as a more economical and efficient model to study the development of cataract. Inspired by these experiments, we investigated whether exposure of young bovine lenses to HBO for 15 h could also serve as a suitable acute model of ARN cataract. We found that while this model is able to exhibit some of the biochemical and physiological changes associated with ARN cataract, the decrease in lens power we observed was more characteristic of the hyperopic shift in refraction associated with ageing. Future work will investigate whether HBO treatment to age the bovine lens in combination with an oxidative stressor such as UV light will induce refractive changes more closely associated with human ARN cataract. This will be important as developing an animal model that replicates the changes to lens biochemistry, physiology and optics observed in human ARN cataracts is urgently required to facilitate the identification and testing of anti-cataract therapies that are effective in humans. Highlights: Highlights Frank Giblin's work to mimic nuclear cataracts with hyperbaric oxygen. HBO exposure of guinea pigs causes changes to the lens nucleus. HBO exposure of rabbit lenses replicates some changes seen in the in vivo model. Future work will focus on developing the bovine in vitro model.